Polyolefin resin foam, adhesive tape and equipment
Patent Information
- Application Number
- JP2020210401
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-18
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2040-12-18
AI Technical Summary
【0008】 本発明によれば、柔軟性が高く、極度に曲げたり折ったりする場合でも、座屈による折れしわの発生を抑制するポリオレフィン樹脂発泡体、粘着テープ及び機器類を提供することができる。
Smart Images

Figure 0007636890000002 
Figure 0007636890000003 
Figure 0007636890000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyolefin resin foam, an adhesive tape, and a device. [Background technology]
[0002] Polyolefin-based resin foams have excellent flexibility, cushioning properties, and heat insulation properties, and are therefore used in various fields such as in-vehicle applications, electronic devices, consumer devices, and housing construction materials (see, for example, Patent Documents 1 and 2). In recent years, the use of olefin-based resin foams as cushioning materials in small electronic devices such as smartphones and wearable devices has been considered. It is expected that in these small electronic devices, the olefin-based resin foams will be used while being bent at curved surfaces or in a folded state. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-508769 A [Patent Document 2] JP 2020-063355 A Summary of the Invention [Problem to be solved by the invention]
[0004] Olefin-based resin foams may develop wrinkles when bent or folded in small electronic devices. When used in small electronic devices, olefin-based resin foams are sometimes bent at 90 degrees or more, but the wrinkles caused by such bending buckle and do not return to their original shape, remaining as creases, which can cause poor appearance and poor performance.
[0005] In addition, polyolefin resin foams may be folded or bent during production and processing, which may cause wrinkles. Wrinkles that occur during production and processing generally return to their original state, but when locally bent excessively, they may buckle and not return to their original state, remaining as creases.
[0006] Therefore, an object of the present invention is to provide a polyolefin resin foam, an adhesive tape, and devices that are highly flexible and suppress the occurrence of creases due to buckling even when bent or folded extremely. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that a polyolefin resin foam having an 80% compressive strength and thickness within a given range can solve the above problems, and have completed the present invention. That is, the present invention relates to the following [1] to [8]. [1] A polyolefin-based resin foam obtained by foaming a polyolefin-based resin composition containing a polyolefin-based resin, the polyolefin-based resin foam having an 80% compressive strength of 130 kPa or less and a thickness of 0.05 mm or more and 5.0 mm or less. [2] The polyolefin resin foam according to [1], wherein the closed cells are crushed to form open cells. [3] The polyolefin resin foam according to [1] or [2], having a closed cell ratio of 10% or more and 69% or less. [4] Apparent density is 0.01 g / cm 3 More than 0.50g / cm 3 The polyolefin resin foam according to any one of [1] to [3] below. [5] The polyolefin resin foam according to any one of [1] to [4], having a degree of crosslinking of 15% or more and 70% or less. [6] The polyolefin resin foam according to any one of [1] to [5], wherein one or both sides are sliced. [7] A pressure-sensitive adhesive tape comprising the polyolefin resin foam according to any one of [1] to [6] and a pressure-sensitive adhesive layer or a double-sided tape provided on at least one surface of the polyolefin resin foam. [8] A device comprising the polyolefin resin foam according to any one of [1] to [6] or the pressure-sensitive adhesive tape according to [7]. Effect of the Invention
[0008] According to the present invention, it is possible to provide a polyolefin resin foam, an adhesive tape, and devices which are highly flexible and suppress the occurrence of creases due to buckling even when bent or folded extremely. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view showing a compression step of the polyolefin resin foam of the present invention. [Diagram 2] 1 is a photograph showing an enlarged cross section of a foam before the cells are crushed. [Diagram 3] 1 is an enlarged photograph showing a cross section of a polyolefin resin foam of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Polyolefin resin foam] The polyolefin resin foam of the present invention has an 80% compressive strength of 130 kPa or less and a thickness of 0.05 mm or more and 5.0 mm or less. In the present invention, as described below, by appropriately adjusting the cell shape, closed cell ratio, apparent density, crosslinking degree, resin components, compounds blended into the resin, and the like, it is possible to obtain a polyolefin resin foam that has high flexibility and is capable of suppressing the occurrence of creases.
[0011] <80% compressive strength> If the 80% compression strength of the polyolefin resin foam exceeds 130 kPa, the flexibility is reduced, and wrinkles generated when the polyolefin resin foam is folded are not restored and remain as creases. From the viewpoint of increasing flexibility and suppressing the occurrence of creases, the 80% compression strength of the polyolefin resin foam is preferably 120 kPa or less, more preferably 110 kPa or less, and even more preferably 100 kPa or less. Moreover, from the viewpoint of improving mechanical strength and impact absorption, the 80% compression strength of the polyolefin resin foam is preferably 10 kPa or more, more preferably 15 kPa or more, and even more preferably 20 kPa or more. The 80% compressive strength is a value measured using a method conforming to JIS K6767.
[0012] <Thickness> If the thickness of the polyolefin resin foam of the present invention is less than 0.05 mm, it becomes difficult to maintain mechanical strength, and if it exceeds 5.0 mm, it becomes difficult to apply it to various electronic devices. From the above viewpoint, the thickness of the polyolefin resin foam is preferably 0.10 mm or more and 4.5 mm or less. In addition, from the viewpoint of suitable use in small electronic devices such as smartphones and wearable devices, it is more preferably 0.15 mm or more and 1.0 mm or less, and even more preferably 0.20 mm or more and 0.5 mm or less.
[0013] As shown in Fig. 1, the polyolefin resin foam 1 of the present invention is passed between two rolls 10 and 11 rotating at different speeds, and compressed while being subjected to shearing, thereby crushing the closed cells shown in Fig. 2 to form open cells as shown in Fig. 3(a) and (b). Here, the closed cells formed by crushing have cells forming the cells that are folded or curved as shown in Fig. 3(a) and (b), and adjacent cells are connected to each other by being partially destroyed, forming an open cell structure. The polyolefin resin foam has an open cell structure formed in this way, which increases flexibility, reduces 80% compression strength as described above, and is less likely to develop creases.
[0014] The roll to be used is not particularly limited, and examples thereof include rolls whose roll surfaces are metal or resin. In the case of a metal roll surface, the roll surface may be subjected to a surface treatment such as chrome plating. In addition, the roll surface may be appropriately embossed. The foamed polyolefin resin foam 1 passes between two rolls 10 and 11 having different rotation speeds, whereby it is compressed while being subjected to shear. The difference in rotation speed between the two rolls is preferably 0.1 m / min to 2.0 m / min, more preferably 0.2 m / min to 1.5 m / min, and even more preferably 0.3 m / min to 1.0 m / min. When the difference in rotation speed between the two rolls is within the above range, breakage of the polyolefin resin foam is suppressed, and closed cells are crushed to form open cells, thereby imparting flexibility to the polyolefin resin foam. From the above viewpoints, the rotation speed of each roll is preferably 1.5 m / min or more and 5.0 m / min or less, more preferably 2.0 m / min or more and 4.5 m / min or less, and even more preferably 2.5 m / min or more and 4.0 m / min or less. From the above viewpoints, the distance between the rolls is preferably 0.05 mm or more and 1.0 mm or less, more preferably 0.10 mm or more and 0.8 mm or less, and even more preferably 0.15 mm or more and 0.6 mm or less. The thickness of the polyolefin resin foam after being compressed by passing it between two rolls is preferably 0.2 mm or more and 5.0 mm or less, more preferably 0.3 mm or more and 5.0 mm or less, and even more preferably 0.4 mm or more and 5.0 mm or less.
[0015] The polyolefin resin foam may be passed between the rolls once or twice or more, but is preferably passed twice. When passing between the rolls twice, it is preferable to press each of both sides of the polyolefin resin foam against the roll with the faster rotation speed once and against the roll with the slower rotation speed once. In this manner, the multiple cells of the polyolefin resin foam are crushed evenly, and a polyolefin foam without bias in strength, flexibility, etc. can be obtained. After passing the polyolefin resin foam once between a pair of rolls, it is preferable to turn it over and pass it between the same rolls again. When passing the polyolefin resin foam between the rolls three or more times, it is preferable to press each of both sides of the polyolefin resin foam against the roll rotating at a higher speed at least once.
[0016] The polyolefin resin foam of the present invention may be compressed by a roll as described above, and then sliced to control the thickness and to form a plurality of sheets. In this case, the polyolefin resin foam obtained may have only one sliced surface or both sliced surfaces. By slicing, a polyolefin resin foam having a thickness of 1 mm or less can be easily produced.
[0017] <Closed bubble rate> The closed cell ratio of the polyolefin resin foam of the present invention is preferably 10% to 69%, more preferably 15% to 65%, even more preferably 18% to 55%, and particularly preferably 15% to 45%. By setting the closed cell ratio of the polyolefin resin foam to the above upper limit or less, flexibility can be increased, 80% compressive strength can be reduced, and the occurrence of creases can be prevented. In addition, by setting the closed cell ratio to the above lower limit or more, impact resistance, mechanical strength, etc. can be easily improved. The closed cell ratio can be measured by the method described in the Examples.
[0018] <Apparent density> The apparent density of the polyolefin resin foam of the present invention is 0.01 g / cm 3More than 0.50g / cm 3 It is preferable that the density is 0.015 g / cm or less. 3 More than 0.30g / cm 3 More preferably, it is 0.02 g / cm or less. 3 More than 0.2g / cm 3 When the apparent density of the polyolefin resin foam is within the above range, the impact resistance, mechanical strength, etc. are improved, while the flexibility is increased, making it easy to adjust the 80% compressive strength to a desired value.
[0019] <Degree of cross-linking (gel fraction)> The polyolefin resin foam of the present invention is preferably obtained by crosslinking and foaming a polyolefin resin composition. The degree of crosslinking of the polyolefin resin foam of the present invention, expressed as the gel fraction, is preferably 15% to 70%, more preferably 20% to 60%, and even more preferably 25% to 50%. When the degree of crosslinking of the polyolefin resin foam is within the above range, it is easy to adjust the 80% compressive strength to a desired value by increasing flexibility while improving impact resistance, mechanical strength, etc. The degree of crosslinking can be measured by the method described in the Examples.
[0020] <Polyolefin resin foam> The polyolefin resin foam of the present invention is a foam obtained by foaming a polyolefin resin composition. The polyolefin resin composition contains a polyolefin resin as a resin. The polyolefin resin composition will be described in detail below.
[0021] [Polyolefin resin] The polyolefin resin is preferably at least one selected from the group consisting of polyethylene resin, polypropylene resin, and ethylene-vinyl acetate copolymer. These resins may be used alone or in combination of two or more. The foam of the present invention is preferably composed mainly of a polyolefin resin, and specifically, the content of the polyolefin resin is preferably 65% by mass or more based on the total amount of resin components contained in the polyolefin resin composition. When the content of the polyolefin resin is 65% by mass or more, the mechanical strength, flexibility, etc. of the foam can be easily ensured. From these viewpoints, the content of the polyolefin resin is preferably 70 to 100% by mass, more preferably 80 to 100% by mass, and most preferably 100% by mass based on the total amount of resin components contained in the foam resin composition. In the following, the total amount of resin components contained in the polyolefin resin composition is simply referred to as "total amount of resin components".
[0022] <Polyethylene resin> The polyethylene resin may be an ethylene homopolymer, or may be a copolymer of ethylene and a small amount of α-olefin, with ethylene as the main component (preferably 75% by mass or more, more preferably 90% by mass or more of the total monomers). The α-olefin preferably has 3 to 12 carbon atoms, more preferably 4 to 10 carbon atoms, and specific examples thereof include 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, and 1-octene. In the copolymer, these α-olefins may be used alone or in combination of two or more kinds.
[0023] As polyethylene resin, low density polyethylene resin (0.930 g / cm 3 Hereinafter referred to as LDPE), medium density polyethylene resin (0.930g / cm 3 Larger than 0.942g / cm 3 less than 0.942g / cm 3 The polyethylene resin may be a linear low density polyethylene resin (LLDPE). The density of the linear low density polyethylene resin is preferably 0.90 g / cm 3 More than 0.93g / cm 3 More preferably, it is 0.91 g / cm or less. 3 More than 0.93g / cm3 The following is the result. The polyethylene resin may be used alone or in combination of two or more kinds.
[0024] <Polypropylene resin> The polypropylene resin may be a homopolypropylene, which is a homopolymer of propylene, or a copolymer of propylene and a small amount of ethylene and an α-olefin other than propylene, with propylene as the main component (preferably 75% by mass or more, more preferably 90% by mass or more of the total monomers). Examples of the copolymer of propylene with an α-olefin other than ethylene and propylene include a block copolymer (block polypropylene), a random copolymer (random polypropylene), and a random block copolymer. Examples of α-olefins other than propylene include α-olefins having about 4 to 10 carbon atoms, such as 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, and 1-octene, and among these, ethylene is preferred from the viewpoints of moldability and heat resistance. In the copolymer, these α-olefins may be used alone or in combination of two or more kinds. The polypropylene resin may be used alone or in combination of two or more kinds.
[0025] In the present invention, any of polyethylene resin, polypropylene resin, and mixtures thereof polymerized with a polymerization catalyst such as a Ziegler-Natta compound, a metallocene compound, a chromium oxide compound, etc. may be used. For example, by using a polyethylene resin, particularly a linear low-density polyethylene, obtained with a polymerization catalyst of a metallocene compound, a foam having high flexibility and high impact absorption properties can be easily obtained.
[0026] Ethylene-vinyl acetate copolymer The ethylene-vinyl acetate copolymer used as the polyolefin resin may be, for example, an ethylene-vinyl acetate copolymer containing 50% by mass or more of ethylene-derived structural units. Since the ethylene-vinyl acetate copolymer has high compatibility with polyethylene resins and polypropylene resins, the ethylene-vinyl acetate copolymer can be easily used in combination with one or more resins selected from the polyethylene resins and polypropylene resins. The density of the ethylene-vinyl acetate copolymer is preferably 0.92 g / cm 3 More preferably, 0.93 g / cm 3 More preferably, 0.94 g / cm 3 and preferably 0.97 g / cm 3 Less than or equal to 0.96 g / cm 3 The following is the result.
[0027] The resin component in the polyolefin resin composition may be a polyolefin resin alone, or may be a combination of a polyolefin resin and another resin component. For example, a polyolefin resin may be used in combination with an elastomer. As the elastomer, an elastomer having good compatibility with the polyolefin resin is used, and specific examples thereof include ethylene-propylene-diene rubber (EPDM), ethylene-propylene rubber (EPM), and styrene rubber. In addition, as the elastomer, a thermoplastic elastomer may be used. As the thermoplastic elastomer, an olefin-based thermoplastic elastomer, a styrene-based thermoplastic elastomer, and the like may be used. As the elastomer, one of the above components may be used alone, or two or more of them may be used in combination.
[0028] As the polyolefin resin, from the viewpoint of improving the impact absorption and flexibility while lowering the 80% compressive strength to suppress the occurrence of creases, a polyethylene resin is preferable, and among them, a low-density polyethylene resin (LDPE) is more preferable. The low-density polyethylene resin (LDPE) may be used alone, or may be used in combination with other olefin-based resins, or may be used in combination with resins other than olefin-based resins. The content of the low-density polyethylene resin is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on the total amount of resin components contained in the polyolefin resin composition.
[0029] <Foaming agent> The foam of the present invention can be obtained by foaming a polyolefin resin composition containing a resin including a polyolefin resin, a foaming agent, etc. As the foaming agent, a thermal decomposition type foaming agent is preferable. As the thermal decomposition type blowing agent, organic blowing agents and inorganic blowing agents can be used. Examples of the organic blowing agent include azo compounds such as azodicarbonamide, azodicarboxylate metal salts (e.g., barium azodicarboxylate), azobisisobutyronitrile, etc., nitroso compounds such as N,N'-dinitrosopentamethylenetetramine, etc., hydrazine derivatives such as hydrazodicarbonamide, 4,4'-oxybis(benzenesulfonylhydrazide), toluenesulfonylhydrazide, etc., and semicarbazide compounds such as toluenesulfonylsemicarbazide, etc. Examples of inorganic foaming agents include ammonium carbonate, sodium carbonate, ammonium hydrogen carbonate, sodium hydrogen carbonate, ammonium nitrite, sodium borohydride, and anhydrous monosodium citrate. Among these, from the viewpoint of obtaining fine bubbles, and from the viewpoints of economy and safety, azo compounds are preferred, and azodicarbonamide is more preferred. The thermally decomposable foaming agents may be used alone or in combination of two or more kinds.
[0030] The content of the foaming agent in the polyolefin resin composition is preferably 1 to 40 parts by mass, more preferably 3 to 35 parts by mass, and even more preferably 5 to 30 parts by mass, based on 100 parts by mass of the polyolefin resin. By making the amount of the foaming agent equal to or more than the lower limit, the polyolefin resin foam is appropriately foamed, and it is possible to impart appropriate flexibility and impact absorption. In addition, by making the amount of the foaming agent equal to or less than the upper limit, the polyolefin resin foam is prevented from being foamed more than necessary, and mechanical strength, etc. can be improved.
[0031] <Additives> The polyolefin resin composition may contain an antioxidant. Examples of the antioxidant include phenol-based antioxidants such as 2,6-di-t-butyl-p-cresol and pentaerythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], sulfur-based antioxidants such as dilauryl thiodipropionate, phosphorus-based antioxidants, amine-based antioxidants, etc. The antioxidant is blended, for example, in an amount of 0.01 to 5 parts by mass per 100 parts by mass of the polyolefin resin.
[0032] The polyolefin resin composition may contain a foaming aid. Examples of the foaming aid include known auxiliaries and vulcanization accelerators such as zinc oxide, lead oxide, cadmium oxide, magnesium oxide, zinc stearate, cadmium stearate, barium stearate, calcium stearate, zinc acetate, borax, urea, ethanolamine, biurea, dibasic lead phosphite, calcium hydroxide, glycerin, diethylene glycol, dibutyltin dimaleate, alkaline compounds, salicylic acid derivatives, thiourea-based, thiazole-based, sulfamide-based, thiuram-based, and dicarbamic acid-based vulcanization accelerators. The foaming aid is, for example, blended in an amount of 0.05 to 5 parts by mass per 100 parts by mass of the polyolefin resin.
[0033] In addition to the above, the polyolefin resin composition may contain additives that are generally used in foams, such as crosslinking aids, decomposition temperature regulators, nucleating agents, heat stabilizers, colorants, flame retardants, antistatic agents, and fillers.
[0034] [Method of manufacturing polyolefin resin foam] The polyolefin resin foam of the present invention may be produced by a method including a step of compressing a pre-produced foam by passing it between two rolls rotating at different speeds. In addition, the foam may be produced by heating a polyolefin resin composition containing at least a polyolefin resin and a thermally decomposable foaming agent to foam the thermally decomposable foaming agent, and then subjecting the produced foam to a process of compressing the foam to obtain a polyolefin resin foam.
[0035] More specifically, the method for producing a polyolefin resin foam of the present invention preferably includes the following steps (1) to (4). Step (1): A step of obtaining a polyolefin resin composition containing at least a polyolefin resin and a thermal decomposition type foaming agent. Step (2): A step of crosslinking the polyolefin resin composition by irradiating with ionizing radiation. Step (3): Heating the crosslinked polyolefin resin composition to foam the thermally decomposable foaming agent to obtain a foam. Step (4): Compressing the obtained foam by passing it between two rolls rotating at different speeds.
[0036] In step (1), it is preferable to obtain a polyolefin resin composition and mold it into a desired shape such as a sheet (also called a foamable sheet). Although not particularly limited, for example, a resin and an additive are fed to an extruder and melt-kneaded to obtain a polyolefin resin composition, and the polyolefin resin composition is extruded from the extruder to be molded into a sheet. In addition, the polyolefin resin composition may be molded into a sheet by mixing each component and then pressing it. The molding temperature (that is, the temperature during extrusion or pressing) is preferably 50°C or higher and 250°C or lower, and more preferably 80°C or higher and 180°C or lower.
[0037] In step (2), the polyolefin resin composition is crosslinked by irradiating the polyolefin resin composition with ionizing radiation such as electron beams, α-rays, β-rays, γ-rays, etc. Among these, electron beams are preferred from the viewpoints of productivity and uniform irradiation. The type of irradiation with ionizing radiation is not particularly limited, but a sheet-shaped polyolefin resin composition may be irradiated on only one side or on both sides. The acceleration voltage of the ionizing radiation varies depending on the thickness of the composition to be irradiated, but is, for example, preferably 400 to 1,200 kV, more preferably 500 to 1,100 kV, and even more preferably 600 to 1,000 kV. The exposure dose of ionizing radiation may be any amount that can achieve a desired degree of crosslinking without causing surface roughness or cracking, taking into consideration the thickness of the foam sheet to be irradiated, and is usually preferably 0.1 to 10 Mrad, more preferably 0.2 to 5 Mrad, and even more preferably 0.3 to 3 Mrad.
[0038] In step (3), the heating temperature when the polyolefin resin composition is heated to expand the thermally decomposable foaming agent may be equal to or higher than the foaming temperature of the thermally decomposable foaming agent, and is preferably 200 to 300°C, and more preferably 220 to 280°C.
[0039] In step (4), the rotation speed of the rolls and the distance between the rolls are set within the above-mentioned conditions so as to crush the foam and convert the closed cell structure into an open cell structure. The thickness of the compressed polyolefin resin foam may be controlled during the compression process, or may be controlled by further slicing after the compression process.
[0040] In the present production method, the polyolefin resin foam may be stretched in either MD or TD or both. The stretching of the polyolefin resin foam may be performed after the polyolefin resin composition is foamed to obtain a foam, or may be performed while the polyolefin resin composition is foamed. In addition, when the foam is stretched after the polyolefin resin composition is foamed to obtain a foam, the foam may be stretched while maintaining the molten state at the time of foaming without cooling the foam, or the foam may be stretched after cooling the foam and heating it again to a molten or softened state. The foam is easily made thin by stretching. In addition, the foam may be heated to, for example, 100 to 280°C, preferably 150 to 260°C during stretching. In the present invention, the foam is stretched to increase the cell diameter of the foam along either MD or TD or both, making it easier to control the thickness.
[0041] However, the present production method is not limited to the above, and a foam may be obtained by a method other than the above. For example, instead of irradiating ionizing radiation, crosslinking may be performed by a method in which an organic peroxide is blended in advance with a polyolefin resin composition, and the polyolefin resin composition is heated to decompose the organic peroxide.
[0042] [Adhesive tape] The adhesive tape of the present invention is an adhesive tape using the above-mentioned polyolefin resin foam of the present invention as a substrate, and specifically comprises the polyolefin resin foam of the present invention and an adhesive layer or double-sided tape provided on at least one side of the polyolefin resin foam of the present invention. The pressure-sensitive adhesive tape of the present invention uses the polyolefin resin foam of the present invention as a substrate, and has a pressure-sensitive adhesive layer provided on one or both sides of the polyolefin resin foam. The thickness of the pressure-sensitive adhesive tape is usually about 0.5 to 2.0 mm. The thickness of the adhesive layer constituting the adhesive tape is preferably 50 to 200 μm, more preferably 80 to 150 μm. When the thickness of the adhesive layer constituting the adhesive tape is 50 to 200 μm, the thickness of the adhesive tape can be made thin, and the adhesive tape can be placed in a narrow space such as a small electronic device.
[0043] The adhesive layer may be any adhesive layer having at least an adhesive layer, and may be an adhesive layer alone laminated on at least one surface of the polyolefin resin foam, or a double-sided tape attached to at least one surface of the polyolefin resin foam. However, from the viewpoint of thinning, it is preferable to be an adhesive layer alone. The double-sided tape includes a substrate and adhesive layers provided on both sides of the substrate. The double-sided tape is used to adhere one adhesive layer to a resin foam sheet and to adhere the other adhesive layer to another member.
[0044] The adhesive constituting the adhesive layer is not particularly limited, and for example, an acrylic adhesive, a urethane adhesive, a rubber adhesive, a silicone adhesive, etc. may be used. Furthermore, a release sheet such as release paper may be further attached onto the adhesive material. The pressure-sensitive adhesive tape using the foam of the present invention can be used as a shock absorbing material, a sealing material, etc. to be installed inside the main body of an electronic device. In addition, the polyolefin resin foam may be bonded to the above-mentioned surface material by the pressure-sensitive adhesive layer of the pressure-sensitive adhesive tape.
[0045] [Equipment] The polyolefin resin foam or adhesive tape of the present invention has high flexibility and can be used in electronic devices including consumer devices such as AV devices, televisions, and washing machines, and transportation devices such as automobiles, ships, trains, and aircraft, and is suitable for use in small electronic devices because it has high flexibility even when it is thin. Examples of small electronic devices include mobile phones such as smartphones, wearable devices, game devices, electronic organizers, tablet terminals, and notebook personal computers. Furthermore, since the polyolefin resin foam or pressure-sensitive adhesive tape of the present invention can suppress the occurrence of creases due to buckling even when extremely bent or folded, it is preferably used in electronic devices having curved surfaces, electronic devices that are used while being folded, such as foldable smartphones, electronic paper, wearable devices, etc. The polyolefin resin foam or pressure-sensitive adhesive tape of the present invention is used while being bent or folded in electronic devices having curved surfaces, or electronic devices that are used while being folded. The polyolefin resin foam or adhesive tape can be used, for example, as a sealing material or shock absorbing material inside devices such as electronic devices. The polyolefin resin foam or adhesive tape may also be used as an interior material in various transport devices, and is preferably used as an interior material for automobiles. EXAMPLES
[0046] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0047] [Measurement method] The methods for measuring the various physical properties in this specification are as follows.
[0048] <80% compressive strength> The 80% compressive strength was measured for the polyolefin resin foam in accordance with JIS K6767:1999.
[0049] <Thickness> The thickness of each polyolefin resin foam was measured with a dial gauge.
[0050] <Apparent density> The density (apparent density) of the polyolefin resin foam was measured in accordance with JIS K7222:2005.
[0051] <Closed bubble rate> A planar square test piece with a side length of 5 cm was cut out from the polyolefin resin foam. The thickness of the test piece was then measured to calculate the apparent volume V1 of the test piece, and the weight W1 of the test piece was also measured. Next, the volume V2 occupied by the air bubbles was calculated based on the following formula. The density of the test piece was ρ (g / cm 3 ) Volume occupied by bubbles V2=V1-W1 / ρ Next, the test piece was submerged in distilled water at 23°C to a depth of 500 mm from the water surface, and a pressure of 15 kPa was applied to the test piece for 3 minutes. After that, the test piece was taken out of the water, and the water adhering to the surface of the test piece was removed. The weight W2 of the test piece was then measured, and the closed cell ratio F1 was calculated based on the following formula. Closed bubble rate (%) = 100-100 × (W2-W1) / V2
[0052] <Degree of cross-linking (gel fraction)> A test piece of about 100 mg was taken from the polyolefin resin foam, and the mass A (mg) of the test piece was precisely weighed. Next, this test piece was immersed in 30 cm of xylene at 120 °C. 3 After immersion for 24 hours, the insoluble matter on the wire mesh was collected by filtration through a 200-mesh wire mesh and dried in vacuum, and the mass B (mg) of the insoluble matter was precisely weighed. The degree of crosslinking (%) was calculated from the obtained value using the following formula. Crosslinking degree (%)=100×(B / A)
[0053] <Practical evaluation (fold and wrinkle evaluation)> A rectangular test piece with a short side of 50 mm and a long side of 100 mm was cut out from the polyolefin resin foam. The rectangular test piece was folded back at the center of the long side, and a load of 100 g was applied and left for 10 seconds. The load was then removed, and the presence or absence (length) of creases on the surface of the test piece was visually confirmed after 10 minutes. A: The length of the crease is between 0mm and 5mm B: The length of the crease is more than 5 mm and less than 10 mm C: The length of the crease is more than 10 mm
[0054] [Raw materials used] The materials used in the examples and comparative examples are as follows.
[0055] <Polyolefin resin> LDPE: Japan Polyethylene Corporation "LE520H" (density: 0.923g / cm 3 , Melt flow rate: 4.0g / 10min)
[0056] <Composition> Foaming agent: "ACK3-TA" (azodicarbonamide) manufactured by Eiwa Kasei Co., Ltd. Antioxidant: ADEKA Corporation's "ADEKA STAB 328" (phenolic antioxidant) Foaming agent: Sakai Chemical's "SZ2000" (zinc stearate)
[0057] Example 1 100 parts by mass of polyethylene resin (LDPE), 20 parts by mass of foaming agent, 0.5 parts by mass of antioxidant, and 1.0 part by mass of foaming assistant were melt-kneaded and pressed to obtain a foamable sheet having a thickness of 1.1 mm. The front and back surfaces of the obtained foamable sheet were irradiated with 2.0 Mrad of electron beam at an accelerating voltage of 800 keV to crosslink the foamable sheet. Next, the crosslinked foamable sheet was heated to 250°C to foam, and the apparent density was 0.020 g / cm. 3 A foam with a thickness of 2.0 mm and a crosslinking degree of 31% was obtained. The distance between rolls 1 and 2 was 0.15 mm, and the obtained foam was passed between rolls 1 rotating at a speed of 3.0 m / min and roll 2 rotating at a speed of 3.6 m / min, and compressed. Thereafter, the foam was turned over and passed again between rolls 1 and 2, and compressed. The thickness of the polyolefin resin foam after passing through the rolls was 2.0 mm. Rolls 1 and 2 were chrome-plated rolls, and the temperatures of rolls 1 and 2 were room temperature (about 23° C.). The polyolefin resin foam that had been subjected to the compression step was sliced to a thickness of 0.2 mm. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0058] Example 2 The same procedure as in Example 1 was carried out except that the polyolefin resin foam that had been subjected to the compression step was sliced to a thickness of 0.3 mm. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0059] Example 3 The formulation of the polyolefin resin composition was changed as shown in Table 1, and the obtained foam was compressed by passing it between rolls 1 and 2, which had a distance of 0.1 mm between rolls 1 and 2, and a rotation speed of 3.0 m / min and a rotation speed of 4.8 m / min. The thickness of the polyolefin resin foam after passing through the rolls was 0.4 mm. The polyolefin resin foam that had been subjected to the compression step was not sliced. The rest of the procedure was the same as in Example 1. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0060] Example 4 The same procedure as in Example 1 was carried out except that the polyolefin resin foam that had been subjected to the compression step was sliced to a thickness of 1.0 mm. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0061] Example 5 The distance between rolls 1 and 2 was set to 0.4 mm, and the foam was passed through to compress it. The thickness of the polyolefin resin foam after passing through the rolls was 5.0 mm. The polyolefin resin foam that had been subjected to the compression step was sliced to a thickness of 2.0 mm. The rest of the procedure was the same as in Example 1. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0062] Example 6 Except for not slicing the polyolefin resin foam that had been subjected to the compression step, the same procedure as in Example 1 was carried out. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0063] Example 7 Except for not slicing the polyolefin resin foam that had been subjected to the compression step, the same procedure as in Example 5 was carried out. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0064] Example 8 The same procedure as in Example 1 was carried out except that the formulation of the polyolefin resin composition was changed as shown in Table 1 and the polyolefin resin foam that had been subjected to the compression step was not sliced. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0065] Comparative Example 1 The distance between rolls 1 and 2 was 0.4 mm, and the obtained foam was passed between rolls 1 rotating at a speed of 3.0 m / min and roll 2 rotating at a speed of 9.0 m / min to compress it. The thickness of the polyolefin resin foam after passing through the rolls was 5.0 mm. The polyolefin resin foam that had been subjected to the compression step was not sliced. The rest of the procedure was the same as in Example 1. Since the obtained polyolefin resin foam was damaged, it was not evaluated for creases, and the 80% compression strength and closed cell ratio were not measured.
[0066] Comparative Example 2 The same procedure as in Example 1 was carried out except that the formulation of the polyolefin resin composition was changed as shown in Table 1, and the compression step was not performed and the polyolefin resin foam was not sliced. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0067] Comparative Example 3 The composition of the polyolefin resin composition was changed as shown in Table 1, and the polyolefin resin foam was sliced to a thickness of 1.0 mm without undergoing a compression step. The rest was the same as in Example 1. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0068] Comparative Example 4 The composition of the polyolefin resin composition was changed as shown in Table 1, and the polyolefin resin foam was sliced to a thickness of 0.5 mm without undergoing a compression step. The rest was the same as in Example 1. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0069] Comparative Example 5 Except for not passing through the compression step and not slicing the polyolefin resin foam, the same procedures were carried out as in Example 1. The evaluation results of the obtained polyolefin resin foam are shown in Table 1.
[0070] [Table 1]
[0071] As is clear from the above results, it is found that the polyolefin resin foam of the present invention can suppress the occurrence of wrinkles. [Explanation of symbols]
[0072] 1...Polyolefin resin foam 10,11…Roll
Claims
1. A polyolefin resin foam obtained by foaming a polyolefin resin composition containing a polyolefin resin and a thermal decomposition type foaming agent, The 80% compressive strength is 130 kPa or less, The thickness is 0.05 mm or more and 5.0 mm or less, The closed cell rate is 10% or more and 69% or less, A polyolefin resin foam in which closed cells are crushed to form open cells.
2. A polyolefin resin foam obtained by foaming a polyolefin resin composition containing a polyolefin resin and a thermal decomposition type foaming agent, The 80% compressive strength is 130 kPa or less, The thickness is 0.05 mm or more and 5.0 mm or less, The closed cell rate is 10% or more and 69% or less, A polyolefin resin foam having an open-cell structure in which cells forming the bubbles have a folded or curved shape and adjacent cells are connected to each other by partially destroying the cells.
3. Apparent density is 0.01 g / cm 3 0.50g / cm or more 3 The polyolefin resin foam according to claim 1 or 2, which is:
4. The polyolefin resin foam according to any one of claims 1 to 3, having a degree of crosslinking of 15% or more and 70% or less.
5. The polyolefin resin foam according to any one of claims 1 to 4, wherein one or both sides are sliced.
6. 6. An adhesive tape comprising the polyolefin resin foam according to claim 1 and an adhesive layer or a double-sided tape provided on at least one surface of the polyolefin resin foam.
7. A device comprising the polyolefin resin foam according to any one of claims 1 to 5 or the pressure-sensitive adhesive tape according to claim 6.
Citation Information
Patent Citations
Preparation of open-cell foam of crosslinked olefinic resin
JP2001040128A
Cushioning material for electronic equipment
JP2013203792A
Automatic magnetic flow recording device
JP2018508769A
Polyolefin resin foam sheet, and adhesive tape
JP2019065252A
Crosslinked polyolefin-based resin foamed sheet, method of producing crosslinked polyolefin-based resin foamed sheet, and adhesive tape
JP2020063355A